Incomplete adherence to an adjunctive systemic antibiotic regimen decreases clinical outcomes in generalized aggressive periodontitis patients: a pilot retrospective study - Adrian Guerrero (Blackwell Synergy, 2007)
Aim: The objective of this study was to explore the effect of incomplete adherence to the prescribed antibiotic regimen, amoxicillin and metronidazole, in the non-surgical treatment of generalized aggressive periodontitis (GAP). Methods: This retrospective study included 18 GAP subjects who received a conventional course of full-mouth non-surgical periodontal treatment using machine-driven and hand instruments and an adjunctive course of systemic antibiotics (500 mg amoxicillin and 500 mg metronidazole three times a day for 7 days). Clinical parameters were collected at baseline and at 2 months post-treatment. Self-reported adherence to the prescribed medication regimen was recorded at 2 months. Results: All clinical parameters, except for the mean clinical attachment level (CAL) in sites with initial probing pocket depth (PPD) 43 mm, improved at 2 months in all subjects. PPD reduction was 3.7mm [95% confidence interval (CI) 3.2, 4.3 mm] in deep pockets (X7 mm) and 2.2mm (95% CI 1.9, 2.4 mm) in moderate pockets (4–6 mm), while CAL gain was 2.2mm (95% CI 1.7, 2.6 mm) and 1.2mm (95% CI 0.8, 1.5 mm), respectively. However, only 11 subjects (61.1%) reported full adherence to the medication. In deep pockets (X7 mm), the difference between an adherent and non-adherent/partially adherent subject was 0.9mm (95% CI 0.1, 1.7 mm, ANCOVA, p50.027) in PPD reduction and 0.8mm (95% CI 0.2, 1.9, p50.129) in CAL gain at 2 months. In moderate pockets (4–6 mm) this difference was smaller in magnitude: 0.4mm (95% CI 0.1, 0.9 mm, p50.036) in PPD reduction and 0.2mm (95% CI 0.3, 0.9 mm, p50.332) in CAL gain. Conclusions: Within the limits of this design, these data suggest that incomplete adherence to a 7-day adjunctive course of systemic metronidazole and amoxicillin is associated with decreased clinical outcomes in subjects with generalized aggressive periodontitis.